2014
DOI: 10.1016/j.jjcc.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The “benefits” of the mini-extracorporeal circulation in the minimal invasive cardiac surgery era

Abstract: Mini-extracorporeal circulation (MECC) constitutes a novel miniaturized cardiopulmonary bypass (CPB) circuit, heparin-coated and primed with aprotinin. Its membrane oxygenation is similar to conventional cardio-pulmonary bypass (CCPB), but it is a completely closed-volume system due to the lack of the venous reservoir which has been removed. In a mini circuit, the reservoir is the patient himself. Consequently, air entering the venous cannula is avoided. Nevertheless, the capabilities of MECC have been expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 76 publications
(194 reference statements)
2
15
0
2
Order By: Relevance
“…There was no difference between the groups in red cell or blood product transfusions, total fluid administration or blood loss in the first 12 h (Table 3). Median (IQR [range]) ICU length of stay was 2 (2-2 [1][2][3][4]) days in the control group and 2 (2-2 [1][2][3][4][5][6]) days in the Hemosep group. There were no deaths.…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference between the groups in red cell or blood product transfusions, total fluid administration or blood loss in the first 12 h (Table 3). Median (IQR [range]) ICU length of stay was 2 (2-2 [1][2][3][4]) days in the control group and 2 (2-2 [1][2][3][4][5][6]) days in the Hemosep group. There were no deaths.…”
Section: Resultsmentioning
confidence: 99%
“…(19) The conventional system is much more forgiving. (20) The danger of air during true open-heart surgery is more real, and, therefore, as a local decision policy, no heart valve surgery with MECC was done. However, Baumbach, et al and Wang, et al reported a superior outcome of MECC in a population of valve surgery.…”
Section: Minimal Extracorporeal Circulationmentioning
confidence: 99%
“…Targeted mechanism Clinical effect Reference [57]. Standard CPB circuits need large priming volumes, which lead to significant haemodilution associated with reduced blood oxygen transport capacity and impairment of coagulation [58].…”
Section: Approachmentioning
confidence: 99%